PERSEPSI MAHASISWA/I PENJASKESREK TERHADAP MATA KULIAH PENCEGAHAN DAN PERAWATAN CEDERA OLAHRAGA UNIVERSITAS ISLAM RIAU TAHUM AJARAN 2018/2019 - Novia Nazirun; Dea Kesfila Fitri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Injury prevention and treatment material is part of the courses in Physical Education Health and Recreation. With this course, it is necessary to provide students with material on preventing and treating sports injuries to them. With this subject, students' perceptions about learning arise. This study aims to determine the perceptions of the fourth semester students of Social Security about injury, prevention and treatment of sports injuries at Riau Islamic University. This research is a quantitative descriptive study with data collection techniques using a questionnaire or questionnaire. The population in this study were all semester IV students of Penjaskesrek, Riau Islamic University, totaling 210 people. The data analysis technique used in this study is descriptive statistics with percentages. The subjects in this study were the fourth semester students of Penjaskesrek at Riau Islamic University, with a total sample of 30 students. Based on the results of research and discussion, it can be described perceptions of semester IV students of Physical Education about injury, prevention and treatment of sports injuries in Penjaskesrek, Islamic University of Riau as follows, the category of